NATIONAL PATRIOTIC EDUCATION OF FUTURE SOCIAL WORKERS AT STUDY PROCESS - Тімкін, І.; Новікова, Н. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
In today`s conditions of challenges and threats for the Ukrainian state the definition of a new strategy of education as a multi-component and multi-vector system, which largely shapes the future development of our country, becomes relevant. Patriotic education of youth has a clear target orientation – to prepare for the defense of the homeland, and is an important component of the system of ensuring the national security of Ukraine. An integral part of patriotic education, and in times of military threat a priority, is a military patriotic education, oriented towards the formation of citizens` readiness to protect, and if necessary, and give their lives to their homelands. The cultivation of patriotism as a component of student`s worldview, his attitude towards the homeland, anther nations and peoples, language, feeling of responsibility for its independence, preservation of material and spiritual values, should become a priority direction of society`s development. Especially it concerns of future social worker as an agent for social change, who in his professional activities can influence the formation of political consciousness and civic position. This article considers approaches to understanding of national patriotic education of future social workers as a system of measures aimed as forming of a “new” Ukrainian, who acts on a basic of national and European values. The concept of patriotism is determined as integral value and moral and spiritual quality of personality